Pozzolanic reaction mechanism of rice husk ash in concrete: a review - Saad , Siti Asmahani; Nuruddin, Muhd Fadhil; Shafiq, Nasir Shafiq; Ali, Maisarah (2014)
Recently, incorporation of cement replacement material (CRM) in concrete has gained considerable attention throughout the world. It is known that the commonly used CRM in current concrete industry is silica fume (SF), pulverized fuel ash (PFA) and rice husk ash (RHA). RHA is an agricultural waste from rice milling process. Rice farming activities is one of the main crops planted in Malaysia and therefore, the rice husk abundantly generated every year. RHA exhibits positive pozzolanic reaction during concrete strength development. The material contains amorphous silica and hence it contributed towards enhancement of various concrete properties. This paper presents a short review of RHA properties as CRM and pozzolanic reaction determination. Keywords: Rice husk ash; concrete; properties of rice husk ash; pozzolanic reaction determination.